Book Review: Reality or Fiction? - Roeland Paardekooper (EXARC Journal)
In October 2018, a conference took place in Southern Poland. It was attended mainly by people from Poland and Slovakia, but also included several EXARC members from abroad. The conference was titled “Archaeological Open-Air Museums: Reconstruction and Reenactment – Reality or Fiction?” which is also the title of this book which was published in 2022. The conference was the result of a cooperative project between Poland and Slovakia and took place at the Carpathian Troy Archaeological Open-air Museum near Krosno, Poland. The conference was reviewed in the EXARC Journal here: https://exarc.net/issue-2019-3/mm/conference-review-trzcinica-2018